World food trends and future food security: meeting tomorrow's food needs without exploiting the environment - Pinstrup-Andersen, Per (International Food Policy Research Institute, 1994)
In World Food Trends and Future Food Security, an IFPRI Food Policy Report, Director General Per Pinstrup-Andersen looks at recent world food trends and asks if the positive production trends of the past 30 years are likely to continue. Or, as 100 million new people are added to the world's population each year, will Malthus' prediction of increasing food scarcity come true? Will food scarcity, hunger, and disease related to malnutrition become even more widespread in the next 20-30 years?